Relações de gênero e seus efeitos discursivos na constituição de subjetividades nos cursos de Engenharia do Campus Universitário de Tucuruí – CAMTUC/UFPA - ALMEIDA, Edileuza de Sarges (Universidade Federal do Pará, 2017)
The research discusses the discursive effects of gender relations involved in the formation of subjectivities in the engineering courses of Tucuruí’s university campus from the Federal University of Pará (UFPA). The study problematizes the gender discursive constructions related to the feminine presence in the Civil, Electrical and Mechanical engineering courses of CAMTUC/UFPA, especially for being related courses to the exact sciences, emerged in 2005 through an agreement between UFPA and Eletrobrás/Eletronorte, and also are considered historically masculine. In the theoretical and methodological field, the text is located in a post-structuralist perspective, dialoguing with Foucault (2011, 2004) and the sexuality studies with Scott (1995) and Louro (2003, 2007, 2013) about the gender as a historical category, political and relational; Swain (2000),Weeks (2001), Beauvoir (2009) and discussions on women and feminism; Apple (2006), Silva (1996, 2010, 2013), Moreira and Candau (2003) with the deliberation about résumé, comprehended as a cultural artifact crossed by power relations; Cabral and Oliveira (2011), Tebet (2008), Lombardi (2006) and Teixeira (2001), about the female insertion in the engineering. The data collection focuses the official curriculums of the mentioned courses and interviews done with female and mans students and managers from the engineering courses, whose documents and narrative analysis indicate a subjectivity discursive production in permanent conflict on gender issues in the surveyed courses, therefore, now the speeches reaffirm woman domination practices historically settled in our society, now transpose these domination barriers by the bias of the uniqueness female attendance, unveiling new training scenarios. The study results argue that the denaturalization of training and professional environment is a prerequisite in order that women can construct their gender, personal and professional subjectivities, with complete freedom, experiencing their own choices and not being restricted to normative standards and stereotypes historically kept. Thus, the study relevance consists in seeking denaturalize the local curriculums and the discursive practices involved in the subjectivities women production in higher education and, along with it, affirm the uniqueness female in professional reconfiguration compared to the historical invisibility and domination onslaught.